Implementation of food matrix effects into chemical food contaminant risk assessment - Cioca, Ana‐Andreea; Langerholc, Tomaz; Tušar, Livija (EFSA journal, 2022)
Food risk assessment plays an important role in protecting public health worldwide. Stakeholders involved in food risk assessment, such as national authorities, agencies, non‐governmental organisations (NGOs), industry and consumers, need to properly understand the terminology of food risk assessment effectively. In this respect, the first part of the EU‐FORA work programme (WP1) aimed to provide insights into the actual translation of two essential terms used in food risk assessment. ‘Hazard’ and ‘risk’ were first identified and compared between the English version of various food regulations and their equivalents in the national legislation of EU Member States. The comparison and critical evaluation revealed several inconsistencies. These inconsistencies could lead to misinterpretations, followed by errors in conducting risk assessments or communicating risks. We recommend that consistency is restored and maintained so that the message is properly communicated. The second part of the work programme (WP2) was focused on a specific area within chemical risk assessment (CRA). In this context, special attention was given to the impact of the food matrix on the bioaccessibility and bioavailability of heavy metals and metalloids. After collection and careful selection of data from scientific journals, a database with information on the bioaccessibility and bioavailability of cadmium (Cd), lead (Pb), mercury (Hg) and arsenic (As) in different food matrices was created for future statistical analyses related to dietary exposure.